"A feminine brand? Never!" Brands as gender threats for "resistant" masculinities. Issue 3 (11th June 2018) - Ulrich, Isabelle; Tissier-Desbordes, Elisabeth
Abstract : Purpose: The purpose of this paper is to examine the relationships between men and brands and specifically how they configure their masculinities in relation to daily used brands. Design/methodology/approach: In-depth interviews with projective technique were conducted with 20 men with different masculinities and sexual orientations to explore their practices regarding and relations to various product categories and brands. Findings: First, this paper shows how men's relationships to daily used brands vary according to different forms of masculinities, in a continuum apparently disconnected from sexual orientation. Men with "resistant" masculinities are strongly attached to choosing masculine brands; others with more hybrid masculinities are more open to feminine brands and do not care about brand gender. Second, this paper shows the importance of brand gender salience: Men with more traditional masculinities interpret brands through the prism of gender first and over-interpret gendered cues in brand execution. Third, feminine brands are considered as threats for men with traditional masculinities. Fourth, brand extensions to the opposite sex are criticized by men with more traditional masculinities but appreciated by men with hybrid masculinities, independently of sexual orientation. Originality/value: This paper investigates the relationships between men and brand gender for daily used brands, by introducing a diversity of masculinities. Furthermore, it builds on a qualitative approach to capture individuals' diverse masculinities. This helps capture the complexity of gender and better understand the relationships between men, masculinities and brands.